Vaccine coverage by social strata in state capitals in the Brazilian Midwest region: a household survey of children born in 2017 and 2018 - Jaqueline Costa Lima; Érica Marvila Garcia; Sandra Maria do Valle Leone de Oliveira; Wildo Navegantes de Araújo; Emmanuela Maria de Freitas Lopes; Sheila Araújo Teles; Karlla Antonieta Amorim Caetano; Ana Izabel Passarela Teixeira; Bárbara Manuella Cardoso Sodré Alves; Ana Paula França; José Cássio de Moraes; Carla Magda Allan Santos Domingues; et al. (Epidemiologia e Serviços de Saúde)
ABSTRACT Objective To analyze full vaccination coverage in live births in 2017 and 2018 in the capitals of the Midwest region of Brazil, according to social strata. Methods Population-based household survey with cluster sampling. Full coverage in children at 12 and 24 months of age and sociodemographic factors were analyzed. Results 5,715 children were analyzed. Full coverage at 12 months of age was 67.9% (95%CI 65.4;70.4), while at 24 months it was 48.2% (95%CI 45.3;51.1). Pneumococcal vaccine had the highest vaccination coverage (91.3%), while the second dose of rotavirus vaccine had the lowest (74.2%). In Campo Grande, no vaccine reached coverage above 90%, with BCG (82.9%) and hepatitis B (82.1%) standing out. Campo Grande and Brasília had the worst vaccination coverage in the high social stratum (24 months of age). Conclusion Vaccination coverage in the Midwest was below 80%, falling short of the recommended target and associated with socioeconomic factors.